Knowledge, Attitude and Practices of Eye Health Care among University of Ghana Graduate Students. - Titiati, P.E. (University of Ghana, 2019)
Background Population growth and ageing are increasing the number of people who are having increase demand for eye care (WHO, 2018; Baidoo, 2009). Disease of the eye accounts for visual impairment and blindness. Blinding and non-blinding eye diseases account for ocular morbidity and is a devastating factor of health. The youth form the working force of any country. They require good eye health to remain active and productive in all aspects of lives. Moreover, 80-90% of blinding eye conditions are preventable when detected early, by forming the right attitude of regular check-up. Graduate students, majority are youth and have achieved the highest level of education, they have larger roles they play in the secular work, they have responsibility towards their families and have influence on their families. Objective: To assess the knowledge, attitude, and practices of eye health among University of Ghana Graduate Students. Methods The study was a cross-sectional study using quantitative method. A self-administered questionnaire was used to collect data on demographic characteristics, vision and health history, knowledge level of eye conditions, attitude towards eye health and practices of eye health with guide from selected previous studies. A stratified sampling process was used select 403 graduate students from all the four colleges in the university excluding all eye health personnel such as ophthalmologist, optometrist, ophthalmic nurses and opticians. A proportionate sampling was used to arrive at the numbers from schools under each college. Every 3rd graduate student who consented in each school under the various colleges were enrolled. Results: The study comprised of 237 males (58.8%) and 166 (41.2%) females with the mean age 30.6±6.4years. Majority of graduate students 224 (55.6%) were ranged 20-29years. Awareness about glaucoma was the highest 88.09%, cataract was 62.03 and refractive error was 40.45. About 4% have never heard about any of the eye conditions. The overall mean score for knowledge is 7.33±4.26. The mean score for attitude towards eye healthcare was 25.55±2.59. The study found the overall level of knowledge about eye conditions was poor 77.17%, 82.88% had good attitude toward eye health care, their main source of information on eye health care was TV/Radio commercial 39.7%. Out of 403 participants, 334 have ever checked their eyes and 69 of them have never checked their eyes. Good practice was eyes checked in 2years or less was 213 of 403 (52.9%). A multivariate analysis showed a significant association between good knowledge and good attitude on good practice. Conclusion The findings of this study revealed the level of knowledge was poor; attitude towards eye health care was good. However, knowledge is significant factor on attitude that influence practice of eye health care. There is the need to intensify eye health education among graduate students, to increase knowledge and practice so to ensure early detection of eye diseases and management.
MPH.
Keywords: Visual Impairment; Blindness; Cataract; Glaucom; University of Ghana